Gamification in Language Learning: The Effect of Using Wayground on Students’ Understanding of the Simple Past Tense - Alya Nabilah; Sri Suci Suryawati; M. Nawawi (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Mastering the simple past tense is a significant challenge for English as a Foreign Language (EFL) learners, often due to the limitations of traditional, teacher-centered instructional methods. This study investigates the effect of Wayground, the latest evolution of the Quizizz platform, as a digital learning medium to improve students' understanding of the simple past tense. A quasi-experimental design was employed with 65 tenth-grade students, who were divided into an experimental group (n = 35) and a control group (n = 30). Data were collected through pre- and post-tests and analyzed using nonparametric statistical measures: the Wilcoxon signed-rank test and the Mann–Whitney U test. The results revealed a statistically significant difference in learning outcomes favoring the gamified intervention (p = 0.000). Despite individual learning variances, the findings confirm that Wayground fosters a highly interactive and motivating environment that significantly accelerates grammatical competence. These results suggest that integrating modern gamification tools can effectively overcome learning constraints and substantially improve structural grammar pedagogy in English as a Foreign Language (EFL) context.